Mathematical Contribution of Analytical Solution in Biological Control using Asymptotic Approach - Eswari, A. (Discontinuity, Nonlinearity, and Complexity, 2026)
The theoretical model of uncolonised by antagonist, colonised by the antagonist and infected by ther pathogen in the biological control has been discussed. In this article, we present the non-steady state solutions for biological control. The simple analytical expressions of the dimensionless concentrations are derived for non-linear boundary value problem using the variational iteration method. Numerical solutions are obtained and the results are discussed graphically. We also compared our analytical results with numerical simulation, it gives a satisfactory agreement is noted.